"I failed, no matter how hard I tried": A mixed-methods study of the role of achievement in primary school dropout in rural Kenya. (September 2016) - Zuilkowski, Stephanie Simmons; Jukes, Matthew C.H.; Dubeck, Margaret M.
Highlights: Baseline achievement in reading and math predicted late-elementary dropout risk. In interviews, youth began dropout stories with their school performance problems. Children made final decision about whether to drop out, not parents. School quality interventions may reduce dropout risk by improving achievement. Abstract: Initial access to school is nearly universal in Kenya, but many children who enroll drop out before completing primary school. In this mixed-methods study, we use quantitative data from a randomized control trial involving 2666 upper primary-grade students, as well as qualitative data from interviews with 41 schoolchildren, dropouts, and parents, to examine dropout. Poorer baseline performance on literacy and numeracy assessments predicted a higher risk of dropout. Interviews revealed that children are the primary decision-makers rather than parents. Together, these findings suggest that school quality interventions may be an effective means of reducing primary school dropout in this region.